Blessings and Cursings: The Liberating Gift of Profanity in Clinical Pastoral Education - Gilmore, Jeremy (The journal of pastoral care & counseling, 2020)
Profanity, derived from the Latin for “not sacred,” has long been seen as antithetical to spirituality. Social norms around organized religion, respectability, race, gender, etc. compound this perception. In this article, I examine how the use of profanity in Clinical Pastoral Education can help students experience personal, social, and physical freedom. Association of Clinical Pastoral Education outcomes, demographic data, and a student experience provide support for this assertion.